Volume 5A: 42nd Mechanisms and Robotics Conference 2018
DOI: 10.1115/detc2018-85371
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-Printed Needle Driver Based on Auxetic Structure and Inchworm Kinematics

Abstract: Linear actuation is a basic need in robotized manipulation of surgical instruments, that must comply with a challenging environment in terms of safety, compactness and now often compatibility with imaging modalities like CT or MRI. In this paper, we focus on needle manipulation for interventional radiology. We propose a needle driver, i.e. a linear actuator for needle insertion, based on the inchworm principle combined with pneumatic energy. Our first contribution is to propose, model and implement the device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Space in the imaging device is very limited. Step by step motion as performed in [13] is therefore selected.…”
Section: Clinical Requirements and Intended Usementioning
confidence: 99%
See 2 more Smart Citations
“…Space in the imaging device is very limited. Step by step motion as performed in [13] is therefore selected.…”
Section: Clinical Requirements and Intended Usementioning
confidence: 99%
“…We then desire to have a pneumatic chamber to develop forces for the needle translation and rotation. Following [13], the operating pressure is set to 3 bars, and intended displacement and rotation are equal to 2 mm and approximately 5 • . In soft tissues such as liver or kidney, the needle is in interaction with tissues of very low stiffness and the insertion forces are low [19], so they are neglected during analysis.…”
Section: Clinical Requirements and Intended Usementioning
confidence: 99%
See 1 more Smart Citation
“…Hasse et al made use of an auxetic re-entrant structure and proposed a tube-like bending actuator where a difference in pressure between the internal and external surfaces of the tube could generate circumferential actuation [145]. A pneumatic 3D printed needle driver which facilitates linear actuation in surgical instruments was proposed by Pfeil et al [146]. The driver used a re-entrant auxetic structure and was able to move and guide a needle due to the combined effects of pneumatics, inchworm kinematics and multimaterial additive manufacturing.…”
Section: Sensors and Actuatorsmentioning
confidence: 99%
“…Range of motion and lifetime are adapted to medical robots of limited number of uses. It was in addition recently shown that the materials could also endure gamma sterilization [18]. Our second contribution is thus the design of a transformation mechanism in the HSC joint to finally get a hydraulically-actuated revolute joint.…”
Section: Introductionmentioning
confidence: 98%